1998
DOI: 10.1136/bjsm.32.1.11
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of physical activity promotion in primary care office settings.

Abstract: Objective-To assess the eYcacy of physical activity promotion in primary care oYce settings. Design-Systematic review of clinical trials in which the eYcacy of physical activity promotion was investigated in a primary care oYce setting with at least one month of follow up. Subjects-A total of 13 981 adults, aged 17-85+, were included from 203 practices in eight trials assessing physical activity promotion in primary care oYce settings. Main outcome measures-Odds ratios and 95% confidence intervals were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 18 publications
3
48
0
1
Order By: Relevance
“…These results are similar to those obtained by others (13)(14)(15)(16)(17)(18). For example, using data from the 2000 National Health Interview Survey, Honda reported that being middle-aged, having a college degree or higher, and being obese were associated with a higher likelihood of receiving physician advice to exercise (13).…”
Section: Discussionsupporting
confidence: 87%
“…These results are similar to those obtained by others (13)(14)(15)(16)(17)(18). For example, using data from the 2000 National Health Interview Survey, Honda reported that being middle-aged, having a college degree or higher, and being obese were associated with a higher likelihood of receiving physician advice to exercise (13).…”
Section: Discussionsupporting
confidence: 87%
“…Three systematic reviews on the efficacy of physician counseling, however, have called such suggestions into question. [30][31][32] The general consensus of these articles indicated that physician counseling outcomes tend to be modest and short-lived at best. Methodological shortcomings limited the validity of most trials, 32 but even large, wellconducted investigations have yielded mixed results.…”
Section: Counseling Efficacymentioning
confidence: 99%
“…37,38 Addressing the gamut of such factors for each patient during a brief office visit is likely impossible. 39 Consequently, as some researchers have suggested, 31,40 a multidisciplinary approach may be best, wherein providers raise the issue of physical activity in their sedentary patients and refer patients to a support system of allied health professionals that can provide ongoing counseling and follow-up as part of their diabetes education efforts.…”
Section: Broader Implications and Recommendationsmentioning
confidence: 99%
“…Some found overall statistically significant (though modest) results, especially in the short term. 59,60 However, results from other reviews 61,62 were mixed and inconclusive when comparing interventions to usual-care controls. Qualities of successful interventions included multiple contacts with the health care team, behavioral approaches, supervised PA, equipment provision, and frequent patient follow-up.…”
Section: Efficacymentioning
confidence: 99%